PROFESIONALISME GURU DI ERA MODERN: PARADOKS DIGITALISASI DALAM BINGKAI REGULASI SISDIKNAS DAN NILAI PENDIDIKAN ISLAM - Rahmat Eka Ramadhani; Wahyu Bhakti Setiawan; Moh Faizin (STKIP Pesisir Selatan, 2026)
Teacher professionalism is the primary pillar in realizing quality national education, however the gap between the regulatory framework and the actual competency of teacher in the field remains an unresolved issue. This study aims to analyze the dynamics of professionalism among educators in the modern era through the framework of the integration of Law No. 20 of 2003 on the National Education System and the values of Islamic education. This study employs a qualitative approach using library research and content analysis techniques, supplemented by limited empirical validation through reflective interviews with education practitioners. The findings identify the paradox of digitalization as the primary structural challenge, wherein digital transformation which should alleviate teachers’ burdens actually increases administrative burdens and shifts the essence of pedagogical duties. Obstacles to professionalism are multi-layered, both technical and non-technical, and thus cannot be resolved through regulatory intervention alone. The Islamic education perspective offers solutions that transcend the framework of formal competencies through the values of sincerity, trustworthiness, and exemplary conduct as the foundation for teachers’ sustainable intrinsic motivation. This study contributes to the development of a holistic model of teacher professionalism that integrates national regulations, responses to the digital era, and Islamic spiritual values as an intervention that has not been comprehensively examined in previous literature.